Pulutan! Filipino bar bites, appetizers and street eats - Gapultos, Marvin (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2018)
"Influenced by the cuisines of Spain, China and America along with over 100 different cuisines found within the Philippines itself, Pulutan are the fun and flavorful finger foods you eat when you drink! Pulutan! Filipino Bar Bites, Appetizers and Street Eats is the ultimate cookbook for casual entertaining in which as Marvin Gapultos, author of The Adobo Road Cookbook, showcases 54 delightful Pulutan recipes including many of his own creations. Recipes in this book include: Salted "Mani" Bar Nuts Fresh Salad Lumpia Rolls Pineapple Glazed BBQ Bacon Skewers And many more, including tantalizing desserts and cocktails!The recipes are easy to follow and use ingredients readily found in any supermarket or Asian grocery store. The results are tasty, satisfying finger foods that you'll enjoy making and sharing. Expert beverage pairings are suggested for each unique dish so you can amaze your friends and family with exciting Filipino favorites at your next gathering"--Provided by publisher.